X‐Ray Microscopy of Halide Perovskites: Techniques, Applications, and Prospects. Issue 26 (29th January 2020) - Kodur, Moses; Kumar, Rishi E.; Luo, Yanqi; Cakan, Deniz N.; Li, Xueying; Stuckelberger, Michael; Fenning, David P.
Abstract: X‐ray microscopy can provide unique chemical, electronic, and structural insights into perovskite materials and devices leveraging bright, tunable synchrotron X‐ray sources. Over the last decade, fundamental understanding of halide perovskites and their impressive performance in optoelectronic devices has been furthered by rigorous research regarding their structural and chemical properties. Herein, studies of perovskites are reviewed that have used X‐ray imaging, spectroscopy, and scattering microscopies that have proven valuable tools toward understanding the role of defects, impurities, and processing on perovskite material properties and device performance. Together these microscopic investigations have augmented the understanding of the internal workings of perovskites and have helped to steer the perovskite community toward promising directions. In many ways, X‐ray microscopy of perovskites is still in its infancy, which leaves many exciting paths unexplored including new ptychographic, multimodal, in situ, and operando experiments. To explore possibilities, pioneering X‐ray microscopy along these lines is briefly highlighted from other semiconductor systems including silicon, CdTe, GaAs, CuIn x Ga1− x Se2, and organic photovoltaics. An overview is provided on the progress made in utilizing X‐ray microscopy for perovskites and present opportunities and challenges for future work. Abstract : X‐ray microscopy can provide a powerful view into the internal workings of halide perovskite materials and devices by resolving chemical, structural, and electronic properties at the nanoscale. This manuscript provides a comprehensive review of the progress made and insights gained in applying X‐ray microscopy of multiple modalities to halide perovskites and an outlook regarding potential future directions.